“Learning to learn” in Nursing Higher Education - González-Hernando, Carolina; Carbonero- Martín, Miguel Ángel; Lara-Ortega, Fernando; Martín-Villamor, Pedro (Investigación y Educación en Enfermería, 2013)
Objective. This study sought to evaluate improvement in self-directed learning by nursing students at Universidad de Valladolid (Spain) after using problem-based learning methodology. Methodology. Ours was a quasi-experimental research with pre-test and post-test of a single group. The sample consisted of 127 of a 135 total of students from the 2nd degree course in Nursing enrolled in the Sexual and Reproductive Health assignment and who had the opportunity to attend all problem-based learning tutorials in the classroom and student group meetings outside the classroom. The Self-Directed Profile Inquiry Questionnaire instrument (CIPA, for the term in Spanish) by Cazares and Aceves was used for the self-regulated profile assessment, which consists of 41 reactives with options 1-5; the lower the score the better the profile for self-direction. It has five components: planning and selection of strategies, self-regulation and motivation, independence and autonomy, use of experience and critical conscience and interdependence, and social value. Results. The mean age was 23 years, 84.4% were women. The students had a very good scores in their self-regulated learning profile before using problem-based learning (82.5), and after its application, they showed a statistically significant improvement (74.2) both in the overall score and in each of its components. Conclusion. The students' self-regulated profile improved after using problem-based learning, a finding that is of utmost importance to achieve autonomy and self-regulation in learning. The development of the ''learning to learn'' skill allows learning for life, which is necessary in 21st century nursing professionals.